2004
DOI: 10.1242/dev.01118
|View full text |Cite
|
Sign up to set email alerts
|

The first cell cycle after transfer of somatic cell nuclei in a non-human primate

Abstract: Production of genetically identical non-human primates through somatic cell nuclear transfer (SCNT) can provide diseased genotypes for research and clarify embryonic stem cell potentials. Understanding the cellular and molecular changes in SCNT is crucial to its success. Thus the changes in the first cell cycle of reconstructed zygotes after nuclear transfer (NT) of somatic cells in the Long-tailed Macaque (Macaca fascicularis) were studied. Embryos were reconstructed by injecting cumulus and fibroblasts from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 39 publications
6
39
1
Order By: Relevance
“…It was reported that primates were different from other animals, as disarrayed abnormal mitotic spindles with misaligned chromosomes were formed in all SCNT embryos (Simerly et al, 2003). However, in our earlier report, 14.8% of SCNT embryos formed normal spindle and clinical pregnancies were achieved in cynomolgus monkey after SCNT embryos were transferred into the recipients (Ng et al, 2004). There is little information available on the timing of chromatin condensation and dynamic changes in microtubules after SCNT in non-human primate.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…It was reported that primates were different from other animals, as disarrayed abnormal mitotic spindles with misaligned chromosomes were formed in all SCNT embryos (Simerly et al, 2003). However, in our earlier report, 14.8% of SCNT embryos formed normal spindle and clinical pregnancies were achieved in cynomolgus monkey after SCNT embryos were transferred into the recipients (Ng et al, 2004). There is little information available on the timing of chromatin condensation and dynamic changes in microtubules after SCNT in non-human primate.…”
Section: Introductionmentioning
confidence: 83%
“…Procedures for manipulating monkey oocytes have been described (Ng et al, 2004). Briefly, a very small opening on zona pellucida was made by acidic Tyrode solution (pH ϭ 1.8), followed by aspiration of the meiotic spindle with small volume cytoplasm (Ͻ2% of oocyte) under polarized microscopy (SpindleView; CRI, Woburn, MA).…”
Section: Procedures For Somatic Cell Nuclear Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method, when applied to NHPs, has not yet produced any live monkeys. This failure may be related to their complicated genome reprogramming process (Ng et al, 2004;Zhou et al, 2006;.…”
Section: Somatic Cell Nuclear Transfermentioning
confidence: 99%